Sun protection behaviour in organ transplant recipients and non‐transplant patients attending a dermatology outpatient clinic in Sweden: A questionnaire survey. Issue 2 (30th August 2021) - Stenman, Caroline; Gillstedt, Martin; Barck, Lykke; Gonzalez, Helena; Halldin, Christina; Wallinder, Andreas; Paoli, John; Osmancevic, Amra; Claeson, Magdalena
Abstract: Background/purpose: Organ transplant recipients (OTRs) are at high risk of developing skin cancer and are therefore advised to protect their skin against ultraviolet radiation from the sun. Specialized OTR clinics with dermatological follow‐up may improve sun habits among OTRs. In this study, we compared self‐reported sun exposure and sun protection behaviour between OTRs and non‐transplant patients (non‐TPs) and between OTRs with and without special dermatological follow‐up. Methods: Patients from Sahlgrenska University Hospital, Gothenburg, Sweden, completed a sun exposure questionnaire. Between 2011 and 2015, 282 OTRs transplanted in the period 1976‐2014 and 414 non‐TPs were recruited among dermatological outpatients. Participants were stratified into five groups by their status as OTRs or non‐TPs and by attendance to dermatological follow‐up. Results: More non‐TPs than OTRs reported one or more sunburns in the past year, 46% vs. 20%, P  < .0001). More OTRs with than OTRs without dermatological follow‐up reported frequent use of sunscreens (63% vs 44%, P  = .006). More OTRs with follow‐up used one or more sun protection measure such as covering clothes, than other OTRs (54% vs 34%, P  = .016). Conclusion: In this study, OTRs reported less sun exposure than non‐TPs. Specialized dermatological follow‐up seems to improve sun protection behaviour among OTRs. We suggest that specialized OTR clinics should be more broadly implemented.